Analisa Keruntuhan Bendungan Malahayu Kabupaten Brebes Dengan Aplikasi HEC-RAS dan Perhitungan Kerugian Dengan Aplikasi InaSAFE - Muammar, Adhitya Zein; Juwono, Pitojo Tri; Asmaranto, Runi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
In the simulation using HEC-RAS 5.0.7 the part to be simulated is the condition of the Malahayu Dam which collapsed due to 7 conditions causing inundation in the downstream area of the Malahayu Dam. Obtained from 7 conditions of dam collapse, the overtopping collapse scenario is the most extreme collapse scenario with an inundation area of 143.54 km2 with a maximum flood inundation height of 19.943 m. The purpose of this dam collapse simulation is to get the most extreme inundation so that in the next process of the inundation, the calculation of economic losses will be carried out with the help of the InaSAFE application. Losses resulting from the Malahayu Dam collapse scenario cover 53 villages from 6 sub-districts so that the evacuation victims reached 22400 people. With this amount, it can be determined that the Malahayu Dam is a dam with a hazard level 4, which is very high. The estimated losses incurred as a result of this collapse reached Rp. 515,521,114,788. The purpose of this study is to determine the level of danger of a dam, to know the characteristics of the flood, and to know the losses caused by flooding due to dam collapse.